Peran Pemimpin Islami Dalam Optimalisasi Tata Kelola Perusahaan - Elfran Dinata Sitepu; Nuri Aslami (Universitas 45 Surabaya, 2023)
Islamic leadership, a leadership model with transcendental values ​​based on the Koran, However, the sunnah in its current development is observed to be increasingly being applied by Islamic leaders. Less than expected. According to Islam, leadership is trust. because he is the boss of the company, four characters are needed: honesty (shidiq), amanah (trustworthy), fathanah (wise) and tabliq (transparent, open). In fact, leadership must be based on monotheistic principles, Counseling, Justice and Freedom. Consequences of applying Islamic teachings. Our result as a company is to make ends meet for the benefit of our family and our families. Doing business as a good deed.